Informing, Coordinating, and Performing: A Perspective on Functions of Sensorimotor Communication - Vesper, Cordula; Sevdalis, Vassilis (Frontiers in Human Neuroscience, 2020)
Sensorimotor communication is a form of communication instantiated through body move-ments that are guided by both instrumental, goal-directed intentions and communicative, social intentions. Depending on the social interaction context, sensorimotor communication can serve different functions. The aim of this article is to disentangle three of these functions: a) an informing function of body movements, to highlight action intentions for an observer; b) a coordinating function of body movements, to facilitate real-time action prediction in joint action; and c) a performing function of body movements, to elicit emotional or aesthetic experiences in an audience. We provide examples of research addressing these different functions as well as a number of influencing factors, relating to individual differences, task characteristics, and situational demands. The article concludes by discussing the benefits of a closer dialog between separate lines of research on sensorimotor communication across different social contexts.